Case study application of blended learning for an engineering simulation course. - Allen, T.T.; Artis, S.; Afful-Dadzie, A.; Allam, Y. (My University, 2013)
Quality Approaches in Higher Education Vol. 4(1), May 2013 article by Theodore T. Allen, Sharnnia Artis, Anthony Afful-Dadzie, and Yosef Allam. The research was conducted at The Ohio State University. This case study documents the transition of an undergraduate software laboratory from face-to-face only instruction to a blended-learning model motivated, in part, by instructor cost savings. To assure quality in learning outcomes was preserved, we implemented the transition using a randomized experiment. Participating students were randomly assigned to blended (treatment) and traditional (control) groups. Performance was measured by pre- and post-knowledge assessment and quizzes. Attitude was measured by the results of a survey administered at the end of the course. The results show that students’ performance in a purely face-to-face instructional class was not significantly different from that based on a blend of online and face-to-face instruction. In addition, the blended type had significantly more consistently favorable ratings than the purely face-to-face instruction. We conclude that blended learning and our experimental approach could be usefully replicated for other face-to-face software laboratory courses and propose four topics for future research.
Keywords: Quality Approaches in Higher Education - Online Classes